2006
DOI: 10.1097/01.pai.0000151933.04800.1c
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Claudin Proteins in Esophageal Adenocarcinoma and Its Precursor Lesions

Abstract: Claudins are components of tight junctions important in intercellular barriers and cell polarity. The authors identified upregulation of Claudins 3, 4, and 7 in gastric adenocarcinoma using Affymetrix U-133 oligonucleotide microarrays and immunohistochemistry (IHC). While normal gastric mucosa lacked Claudin 3, 4, and 7 expression, intestinal metaplasia and dysplasia showed these proteins. The authors hypothesized that Claudins would be similarly overexpressed in Barrett's esophagus (BE)/adenocarcinoma. Claudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…16 Among various genetic events a disturbed balance of TJ proteins, which regulate tissue integrity and paracellular transport, is believed to promote the development of BC. [17][18][19] In line with this hypothesis complex alterations of TJ expression in BE and BC compared to esophageal squamous epithelium have been observed: claudin-1 and claudin-5 are downregulated in BE 19,20 whereas for claudin-2, -3, -4 and -7 an upregulation has been noted, in particular in highgrade IN and BC. 17,19,21 These data suggest that downregulated TJ proteins might facilitate inhibitory functions, whereas upregulated TJs may promote the progression of BE.…”
Section: Introductionmentioning
confidence: 69%
“…16 Among various genetic events a disturbed balance of TJ proteins, which regulate tissue integrity and paracellular transport, is believed to promote the development of BC. [17][18][19] In line with this hypothesis complex alterations of TJ expression in BE and BC compared to esophageal squamous epithelium have been observed: claudin-1 and claudin-5 are downregulated in BE 19,20 whereas for claudin-2, -3, -4 and -7 an upregulation has been noted, in particular in highgrade IN and BC. 17,19,21 These data suggest that downregulated TJ proteins might facilitate inhibitory functions, whereas upregulated TJs may promote the progression of BE.…”
Section: Introductionmentioning
confidence: 69%
“…This accounts for claudin-7 in breast (53,54) and esophageal cancer (55). However, up-regulated claudin-7 expression was seen in renal (56), cervical (57), and gastric cancer (58,59). This may be a consequence of claudin-7 being not only located in tight junctions, but also at the basolateral membrane and/or in vesicles (7,(60)(61)(62).…”
Section: Introductionmentioning
confidence: 79%
“…In addition, there was a tendency to reduced the claudin-1 expression in the cases with venous clarified in the esophagus extensively. In addition, only several studies examined claudins expression in the esophageal diseases including cancers (6,13,15,23,28). In this study, we demonstrated that decreased expression of claudin-1 was correlated with the recurrence status in esophageal squamous cell carcinoma, and associated with short disease-free survival and overall survival.…”
Section: Evaluation Of Immunostaining Patterns Of Claudin-1mentioning
confidence: 61%
“…The claudins have been suggested to be associated with carcinogenesis and tumor progression. Alteration of claudins has been detected in carcinomas of the esophagus (6,13,15,23,28), colorectum (14,19), and other cancers (16,21,24), suggesting that the claudins are involved in the process of carcinogenesis (20).…”
mentioning
confidence: 99%